2012
DOI: 10.1007/s00217-012-1739-2
|View full text |Cite
|
Sign up to set email alerts
|

Migration of plasticizers from the gaskets of lids into oily food in glass jars: a European enforcement campaign

Abstract: The results of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Details of the samples are given in Table . These were the exact same samples as were purchased and sent for analysis in the enforcement campaign …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the samples are given in Table . These were the exact same samples as were purchased and sent for analysis in the enforcement campaign …”
Section: Methodsmentioning
confidence: 99%
“…In 2012 the results from a Joint European Enforcement Campaign were reported, looking at the composition of plasticisers in gaskets and migration of plasticisers from gaskets of lids into oily foods in glass jars . A total of 308 samples from 21 European countries were tested.…”
mentioning
confidence: 99%
“…Previous studies have shown that ESBO migration represents a serious long-lasting problem (Hammarling et al 1998;Fantoni & Simoneau 2003;Ežerskis et al 2007;Pedersen et al 2008;Bueno-Ferrer et al 2010;McCombie et al 2012McCombie et al , 2015. The producers were unable to deliver lids for oily foods respecting the existing legal limits (Grob & Marmiroli 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Except ESBO, gaskets contained also the considerable amount of polyadipates and minor amount of acetyl tributyl citrate (ATBC), dibutyl sebacate (DBS) and acetylated mono-and diglycerides of fatty acids. The development in lid manufacturing and previous studies indicated that gasket (PVC) plasticised with highly viscous polyadipates diluted with plasticisers of relatively low viscosity or naturally based plasticisers from renewable resources could be the promising alternative to produce metal closures with PVC gaskets complying with the legal limits in oily foods Biedermann, Fiselier, Marmiroli, et al 2008;Vieira et al 2011;McCombie et al 2012;Coltro et al 2014). Other plasticisers were not found in the tested gaskets.…”
Section: Testing Of Esbo Migration From the Lid Into Olive Oil At Varmentioning
confidence: 98%
See 1 more Smart Citation